Insuficiencias jurídicas de la promesa de compraventa en la legislación civil ecuatoriana - Moreno Calderón, Carlos Bernardo (2015)
The Constitution of the Republic of Ecuador under Title II, Chapter I, which speaks of the Principles of the Rights in its article 11 paragraph 1 determines that the exercise of the rights shall be governed by principles like: "Rights they may exercise, promote and enforce individually or collectively to the competent authorities; These authorities will ensure compliance. "Thus, it is important to know that at any time, can demand respect and compensation for rights when they are affected, to the competent authorities. The Constitution also refers in the same paragraph of Article 9: "The highest duty of the State to respect and enforce the rights guaranteed in the Constitution." This means that the State is above any law that violates the rights guaranteed under the rules of this body of law, policy making or reform these laws. From this perspective and in the field of contracts, which carry different obligations and rights for those involved, according to the stipulated by the Constitution and relevant laws, which are the agreements reached by the parties. Thus, there are cases where you can not conclude contracts for different situations; hence there is a promise to conclude a contract of sale. The Civil Code in force presents some inconsistencies and shortcomings with respect to this legal concept, its Article 1570 states: "The promise of entering into a contract produces no obligation;. unless the following conditions: 1. That promise is in writing; and by deed, when he is concluding a contract for the validity of such solemnity required, under the provisions of the Code; 2. The contract promised not to declare the laws ineffective; 3. That the promise contains a term or condition set by the time of conclusion of the contract; and, 4. That specified therein so the contract promised, missing only, to make it perfect, the tradition of the thing, or the formalities prescribed by law. When a promise of sale, which are key elements as the time required to configure, which is set by public deed, and the specification of the tradition, but it happens that this is not allowed registration in the Land Registry is signed, which cause failure by the parties legal uncertainty which entails the right to own insecurity. Hence the need for a research work to establish as another obligation of the promise of sale, registration in the land registry or trade registers, depending on the type of asset, as their lack of registration causes, which in many cases, such goods are misused by their owners and incur double sale or similar cases to it.